Hybrid Laser vs. MAG Welding : Fatigue Behaviour and Reengineering Analysis - Rodas Alfaya, Fernando (2013)
Nowadays automotive industry competence forces companies to employ high productivity fabrication techniques and to design them with reduced weight and optimum structural integrity.The possible measures for this are to introduce new weld methods, so as to allow greater resistance and consequently to reduce the thickness of the component.The main objective in this master’s thesis is to determine the minimum thickness that guarantees an optimum structural integrity of a component used in the automotive industry by a company in Luleå (Sweden) reconsidering its manufacturing design, as well as economic benefits arising from that.This thesis is divided up into two papers:The first paper shows a study about influence of the welding method in the workpieces based in fatigue tests. Equipment used for tests is described with their characteristics, advantages and benefits. Finally, the results and conclusions of the fatigue tests realized in the workpieces are summarized.The second paper shows the calculations and results of the minimum thickness and costs of the workpiece that guarantees an optimum structural integrity. Validerat; 20131219 (global_studentproject_submitter)